Sistem Aplikasi Surat Masuk dan Surat Keluar Berbasis Web pada Dinas Kehutanan Provinsi Sumatera Utara - Wahyuni Fithratul Zalmi (Jurnal Informatika, 2023)
The use of electronic media is expected to help the archive managers to manage their archives effectively and efficiently. By using electronic media in the management of Archives will be obtained the benefits of speed, convenience and savings. The purpose of speed here is through the use of electronic media, the process of searching, discovering, distributing and processing data is carried out in a short time. The purpose of the ease of use of electronic media is the ease in terms of search, distribution and processing of data, which is efficient in the use of electronic media that can reduce energy, mind and save costs in managing archives. With these reasons, at present many organizations / agencies that use electronic media in the management of archives, ranging from simple to sophisticated. At the Forestry Service of North Sumatera Provinceexperience difficulties in the management of receiving and storing various letters, reports, forms and so on. The administration section is one of the parts of the Forestry Service of North Sumatra province of Batujajar. This work Unit manages the archives as the end result of administrative activities. One type of archive that is managed is the Mail Files. This file has not been done electronically.